Establishing fire safety skills using behavioral skills training. Issue 2 (25th April 2014) - Houvouras, Andrew J.; Harvey, Mark T.
<x xml:space="preserve">Abstract</x> The use of behavioral skills training (BST) to educate 3 adolescent boys on the risks of lighters and fire setting was evaluated using in situ assessment in a school setting. Two participants had a history of fire setting. After training, all participants adhered to established rules: (a) avoid a deactivated lighter, (b) leave the training area, and (c) report the lighter to an adult. The response sequence was maintained for both participants after training. The use of in situ assessment to evoke and observe infrequent behavior is discussed.